Encounters with projective identification: Utilising group debrief sessions to contain student teachers’ anxiety - Auld, S.; Haselau, T. (South African Journal of Higher Education, 2024)
Teaching experience ‒ in face-to-face, online, and blended educational contexts ‒ provides student teachers with the opportunity to participate in low, mid, and high-resourced schools, in preparation for their integration into the South African educational system. Often, while at low-resource schools, student teachers report feeling ineffectual, frustrated, despondent, and overwhelmed, leading to criticism of the programme, requests to transfer to high-resource alternatives, and threats to disengage from teaching experience. Drawing on Klein’s concept of projective identification, and Bion’s idea of container-contained, we understand such communications as expressions of overwhelming anxiety, highlighting an urgent need for intervention. To address this need, group debrief was incorporated into teaching experience, in an attempt to enable anxiety to be tolerated, worked through, and understood, rather than evacuated defensively via projective identification. Pre- and post-debrief questionnaires were employed to track containment facilitated with fifty (50) final (4th) year student teachers. Though some resistance was expected and noted, the outcomes were largely positive, with most students reporting improved emotional states, reduced anxiety, and feelings of empowerment.